Reunifying Feature Inheritance and Speech Act Projections: Testing the Model on Peripheral Constructions from Arabic - Saleem Abdelhady (Forum for Linguistic Studies, 2024)
This study aims to bridge a gap between Feature Inheritance (FI) and Speech Act Projections (SAPs), addressing the significant challenge SAPs pose to FI and its underlying mechanism, AGREE. Previous studies highlight the need for reallocating features within the syntax to reconcile FI with cartographic structures, suggesting that moving the C head above Foc and ToP heads is necessary. However, this reallocation is problematic as it fails to account for SAPs, creating a mismatch between syntax and pragmatics, where C must be c-commanded by SAPs rather than simply articulated by them. To address this issue, the study redefines the locus of features in syntactic derivations, proposing that syntactic operations target clausal structures while pragmatic constructions target utterances. Given that every clause is an utterance, but not every utterance is a clause, the study argues that features originate in a head higher than C, identified as U(tterance). This redefinition unifies the use of upward and downward AGREE in the pragmatic-syntactic interface and simplifies grammar by eliminating arbitrary processes like feature sharing. The study tests this new model using data from Arabic, demonstrating that C patterns with other phasal heads such as T and v, inheriting its features from the U head. The findings suggest that this approach provides a more coherent account of the interaction between syntax and pragmatics, with recommendations for further exploration of the model across different languages to validate its applicability and potential to simplify syntactic theory.